(untitled) (Texas Journal of Engineering and Technology, 2022)
The purpose of this work is to study how to improve the anticorrosive properties of lubricants. With an increase in temperature, the combined action of oxygen, air and water present in the lubricating oil causes rusting of the crankshaft, the walls of the sleeves, the cylinders of the internal combustion engine.